2016
DOI: 10.1007/s00382-016-3045-3
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring early-flood season intraseasonal oscillations and persistent heavy rainfall in South China

Abstract: Guangxi and Fujian provinces, has the most abundant rainfall in China (Lu 1990). The rainy season in this area is usually divided into the early-flood season (April-June) and the late-flood season (July-September). During the early-flood season, heavy rainfall events and the associated floods frequently cause severe property damages in South China. The late-flood season rainfall is mainly caused by tropical systems moving into South China, whereas the rainfall during the early-flood season is largely associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…The BSISO influences on precipitation in the Yangtze River Valley are fulfilled via modulating the position of the western Pacific subtropical high (Ren et al 2013;Lu et al 2014). Precipitation extremes also show close relationship with two BSISO components (Hsu et al 2016;Gao et al 2016). For instance, both Lu et al (2014) and Zhu et al (2003) revealed that floods in the Yangtze River Basin during 1998 were in tandem with the active phase of 30-60-day BSISO.…”
Section: Introductionmentioning
confidence: 94%
“…The BSISO influences on precipitation in the Yangtze River Valley are fulfilled via modulating the position of the western Pacific subtropical high (Ren et al 2013;Lu et al 2014). Precipitation extremes also show close relationship with two BSISO components (Hsu et al 2016;Gao et al 2016). For instance, both Lu et al (2014) and Zhu et al (2003) revealed that floods in the Yangtze River Basin during 1998 were in tandem with the active phase of 30-60-day BSISO.…”
Section: Introductionmentioning
confidence: 94%
“…There are two commonly applied techniques in studying ISOs, namely, the ISO indices (e.g., Wheeler and Hendon, 2004;Lee et al, 2013;Lin, 2013;Gao et al, 2016;He et al, 2019;Qian et al, 2019) and the bandpass filter technique (e.g., Tong et al, 2009;Hsu, 2012;Qiao et al, 2015;Hu et al, 2018c). Using the first technique, spatial patterns of ISO modes are extracted by multivariable empirical orthogonal functions (MV-EOFs).…”
Section: Introductionmentioning
confidence: 99%
“…The data used in this study are listed as follows: (a) the National Centers for Environmental Prediction (NCEP)-National Center for Atmospheric Research (NCAR) daily reanalysis data set with a horizontal resolution of 2.5 (Kalnay et al, 1996;Kistler et al, 2001Kistler et al, ) during 1982Kistler et al, -2016(b) the NOAA high resolution SST daily data with a horizontal resolution of 0.25 during the same time which are provided by the NOAA/OAR/ESRL PSD, Boulder, Colorado, USA, from their website at http://www.esrl. noaa.gov/psd/; (c) the TC best-track data sets from the Joint Typhoon Warning Center (JTWC; western North Pacific; data available online at http://metocph.nmci.navy.mil/jtwc/best_ tracks/), where the tropical cyclone genesis location is defined as the position of a storm whose maximum sustained 1-m winds first reaches 17 m/s along its trajectory, a definition identical to McDonald et al (2005); (d) the daily outgoing longwave radiation (OLR) obtained from the NOAA polar orbiting satellites (Liebmann, 1996); (e) three sets of daily real-time ISO indices for the period of 1982-2016, where the RMM indices are downloaded from the Australian Bureau of Meteorology website (http://www.bom.gov.au/climate/mjo/), the BSISO-1 and BSISO-2 indices are from the International Pacific Research Center website (http://iprc.soest.hawaii.edu/users/jylee/bsiso), and the EAWNP ISO-1 and EAWNP ISO-2 indices are calculated according to Lin (2013) and Gao et al (2016).…”
Section: Datamentioning
confidence: 99%
“…Studies indicate that there is an increase of TC genesis in the convective ISO phases while a decrease in the non-convective phases over the WNP basin (Liu and Lin, 1990;Kim et al, 2008;Wang and Zhou, 2008;Gao and Li, 2011;Zhu et al, 2013;Li and Zhou, 2013a;2013b). In addition to the ISO of 30-60-day period, a second dominant mode of ISO with 10-20-day prevailing period, referred to as the quasi-biweekly oscillation (QBWO), has also been identified over the Asian summer monsoon region (Chen and Chen, 1993;Chen and Sui, 2010;Kikuchi and Wang, 2010;Lee et al, 2013;Gao et al, 2016). Previous studies suggested that the kinetic energy of the QBWO is much stronger than that of the MJO over the WNP basin (Li and Zhou, 1995), so the QBWO can strongly impact on the local TC activity (Wang and Chen, 2009;Li and Zhou, 2013a;2013b).…”
mentioning
confidence: 99%
See 1 more Smart Citation